(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Primary Glomerulonephritis (GN) is a heterogeneous group of diseases. Steroids and Immunosuppressives are the mainstay of treatment of this group. The 2012 Kidney Disease Improving Global Outcome (KDIGO) guideline for GN recommends the best evidence based guidelines for GN. After the guideline has been published some of the advances has been seen in some of the trials regarding the use of Rituximab particularly in steroid and Calcineurin (CNI) dependent Minimal change Nephrotic Syndrome(MCNS) and Idiopathic Membranous Nephropathy (IMN). Recently a new entity "Cz glomerulonephritis” has been proposed for which complement directed therapy (Eculizumab) has been suggested. In some recent trials Abatacept has been used in Focal segmental Glomerulosclerosis (FSGS) and Ofatumumab has been used in Rituximab resistant nephrotic syndrome. In our review we will focus on some of key recommendations of KDIGO guideline along with some of the findings made after the guideline has been published. JCMCTA 2014 ; 25 (1): 44-51